2012
DOI: 10.1111/febs.12045
|View full text |Cite
|
Sign up to set email alerts
|

Insulin solubility transitions by pH‐dependent interactions with proinsulin C‐peptide

Abstract: Proinsulin processing into insulin and C-peptide in the secretory granules of the pancreatic b-cells occurs under mildly acidic conditions and at high peptide concentrations (> 10 mM). Mature insulin has reduced solubility and a propensity to adopt an amyloid-like structure, but is physiologically released as a mixture of a zinc-containing core and a zinc-free, C-peptiderich fluid phase. C-peptide is known to function in the insulin secretion, but its exact mode of interaction is not established. We now demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…The importance of the C-peptide negative charge is supported by reports that the position of Glu-3 has co-evolved with hydrophobic and acidic residues in the insulin A-and B-chains [28]. Similarly, all the four most conserved Glu residues seem to correlate with insulin charge interactions and with a 2:1 optimal stoichiometry in insulin/Cpeptide complexes [29]. Further, once the insulin moiety is folded, the C-peptide segment has to adopt a protruding, loop-like structure [30].…”
Section: Conserved Features Linked To Insulin Interactionsmentioning
confidence: 85%
“…The importance of the C-peptide negative charge is supported by reports that the position of Glu-3 has co-evolved with hydrophobic and acidic residues in the insulin A-and B-chains [28]. Similarly, all the four most conserved Glu residues seem to correlate with insulin charge interactions and with a 2:1 optimal stoichiometry in insulin/Cpeptide complexes [29]. Further, once the insulin moiety is folded, the C-peptide segment has to adopt a protruding, loop-like structure [30].…”
Section: Conserved Features Linked To Insulin Interactionsmentioning
confidence: 85%
“…The release profile of a sustained release nano-system is significantly influenced by the chemical nature of the release liquid [29][30][31][32]. The oral dosage is exposed to different pH values and ionic strengths along the GI path.…”
Section: Release Profile Of Insulin From Insulin/plga-hpmc Nanoparticlesmentioning
confidence: 99%
“…Both graphs show a gradual prolonged release with similar trends. It has been reported that the combination of HPMC with water-insoluble polymers retards the release profile in buffer liquids [30,31]. This retardation is attributed to the formation of a strong gel layer with slow erosion and diffusion rates.…”
Section: Release Profile Of Insulin From Insulin/plga-hpmc Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligand binding properties may also differ depending on the localization of the protein and stabilize TTR specifically under aggregation-promoting conditions. A similar example is the regulation of insulin solubility by proinsulin C-peptide, which has a monomerizing effect on insulin at granular pH (71). In the light of this, the molecular interaction networks of TTR in intracellular and extracellular environments may hold valuable information with regard to its roles in health and disease.…”
Section: Trends and Future Directionsmentioning
confidence: 99%